New chiral ligands derived from (+) and (−)-α-pinene for the enantioselective addition of diethylzinc to aldehydes. Issue 3 (20th January 2016) - Frensch, Gustavo; Labes, Ricardo; Wosch, Celso Luiz; Munaretto, Laieli dos Santos; Salomé, Kahlil Schwanka; Guerrero, Palimécio G.; Marques, Francisco A.
Graphical abstract: Abstract: In this study, we synthesized five new chiral ligands from (+) and (−)-α-pinene, which were successfully employed in the stereoselective addition of diethylzinc to aldehydes, leading to secondary chiral alcohols in up to 99% yield and 94% e.e.